Israel e Palestina sob a perspectiva brasileira: política externa e realinhamentos árabes e judaicos - Moraes, Marina Pequeneza de (2016)
The study aims to contribute to the analysis of Brazilian foreign policy regarding the Israeli-Palestinian issue during the establishment of the Israeli State. In order to take the debate further, the research seeks to understand how the existing Arab and Jewish communities in this country campaigned in favour of their own position within the Brazilian policy on this matter. For us to investigate the essential forces and elements in the formation of Brazilian diplomatic positioning, it is crucial we understand how the Palestine issue was discussed and how it shaped within society, according to the 1947 and 1948 events, which determined the establishment of the Arab and Jewish communities in Brazil. It is therefore necessary to emphasise the meaning of both domestic and international scenarios. The study is based upon the analysis of documents related to the Brazilian diplomatic history, available in the archives of Itamaraty Palace - Ministry of External Relations, as well as the archives of the most relevant national newspapers of that period, “Jornal do Brasil”, “Correio da Manhã”, “Folha de São Paulo” and “Estado de São Paulo”, amongst several other sources. By gathering all information available from all sources it is clear to us that the Brazilian government in his diplomacy had to overcome a series of factors, which were previously based on restrictive and pre-judgemental policies existing during this historical period. As a result, the fact that the two groups in question have unique characteristics and beliefs shows us the direct impact towards their mobilisation and the outcome of it